ANALISIS HASIL PENJUALAN DAGING AYAM SELAMA 3 BULAN DENGAN UTILISASI DATA WAREHOUSE - I Wayan Wahyu Ivan Mahendra Jaya; I Putu Agus Eka Pratama (JUSS (Jurnal Sains dan Sistem Informasi), 2022)
UD. Giri Sari as one of the raw whole chicken distributor in the city of Denpasar, Bali that distribute raw chicken to many consument ranging from daily consument to huge food chain industry, until now does not yet have a data-based system to facilitate them analyzing data and simplify their business reports. This study aims to provide proposed solutions in the form of design and implementation related to raw whole chicken stock distributor data for three month, to make it easier to measure the stockpilling distribution of all types of chicken parts and stocks. The implementation uses the open-source Talend Data-Integration and Tableau application to create data integration across all type of file and generate reports for analysis. Data is created in a form of two-dimensional and multi-dimensional design to facilitate the application of data warehouse design that has been created.